FACTORS OF SPREAD OF VIRAL HEPATITIS A INFECTION AND PREVENTIVE MEASURES (Eureka Journal of Health Sciences & Medical Innovation, 2026)
Particular attention is paid to the role of waterborne transmission associated with contaminated drinking water, outdated water supply and sewage systems, and insufficient sanitary control. In addition, socio-demographic factors such as population density, internal and external migration, household crowding, and low levels of health awareness are considered as important determinants of disease transmission. Environmental problems, including water scarcity and ecological degradation, are also examined as indirect factors influencing the epidemiological situation.The research is based on a comprehensive analysis of epidemiological surveillance data, official healthcare statistics, and published scientific sources.
Keywords: viral hepatitis A, epidemiology, transmission factors, preventive measures, waterborne infections, public health.